Aerobic exercise effects on the peripheral plasma lipidome in mild cognitive impairment: The influence of prediabetes: Biomarkers (non‐neuroimaging) / plasma/serum/urine biomarkers. (7th December 2020) - Gross, Thomas J.; Cheema, Amrita K.; Espeland, Mark A.; O'Bryant, Sid; Cotman, Carl W.; Baker, Laura D.; Mapstone, Mark
Abstract: Background: Subclinical glucose intolerance (pre‐Type 2 diabetes; pre‐T2D) likely influences cognitive decline in older adults. Disordered glucose metabolism may itself be a feature of early Alzheimer's disease or mild cognitive impairment (MCI). While aerobic exercise may benefit episodic memory, the plasma lipidomic alterations associated with aerobic exercise in older, at‐risk or cognitively impaired adults remains unclear. Method: We performed a retrospective analysis of 95 participants randomly assigned to Aerobic Exercise ( n = 54) or Stretching ( n = 41) arms in the Piedmont Aging, Cognition, and Exercise (PACE) studies. Analysis of blood lipids was conducted using the QTRAP® 5500 LC‐MS/MS (Sciex) targeted mass spectrometry platform. Co‐expressed lipid modules were identified and submitted to differential expression (DE) analysis. Results: Factorial analysis of co‐expressed lipids revealed a pattern of complex expression heterogeneity. We found a significant metabolic status (pre‐T2D/ MCI/ comorbid) by treatment arm (Aerobic Exercise/ Stretching) by time point (pre/post intervention) interaction ( p = 0.02). Specifically, we see a significant reduction of long chain/ very long chain triacylglycerides (TAGs) in the comorbid (pre‐T2D + MCI) group following aerobic exercise ( p =0.03). Conclusion: These findings suggest a complex interrelationship between aerobic exercise and peripheral dyslipidemia associated with pre‐T2D in the context of MCI. Specifically, we see reductions in TAGs following exercise only when the two risk factors are comorbid, but not when they occur alone. These findings may be of value as biomarkers of exercise‐intervention response and suggest specific populations that may benefit from aerobic exercise. Future study of these interrelated risk factors modifying exercise benefit is warranted to understand which MCI patients will benefit from aerobic exercise.